(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article studies the amount of chlorophyll grains in the leaves of non-traditional oilseed crops during the tillering phases of the growth period. The results of the analysis of the causes and consequences of changes in the amount of chlorophyll grains in the leaves during these periods are reflected.